Pemahaman pelajar Institusi Pengajian Tinggi (IPT) terhadap batas aurat dan pergaulan sosial : kajian di Kolej Matrikulasi Kedah - Mohd Azlan, Md Saad (2016)
Aurat issues are closely related to the problem of social interaction among students in our country. In general, students mingle and interact with each other whether in the classroom learning sessions, co-curricular activities,group assignments and outside classroomactivities. According to Islamic law, to cover themselves and be careful when mixing is an obligation on men and women. However, there are students who cover themselves properly and maintain relationships, while there are also among those who do not cover themselves properly and not keeping the boundary of interaction. Thus, this study aims to determine the level of students' understanding of the limitations of aurat, social interaction and analyze the different levels of their understanding. This study involves 341 Muslim students from Kedah Matriculation College, Changlun, Kedah from the Science and Accounting streams. Data is obtained through the questionnaire, literature study and observation. The study found that the level of students' understanding of the boundary of aurat and interaction is high. In the meantime, there are also students who are less familiar with the demand of the religion. Therefore, the findings provide guidance for the management of the college through Islamic Education Unit and the Counselling Unit to facilitate and help students to behave accordingly to the demands of Islamic law